2006
DOI: 10.1111/j.1468-3083.2006.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Verruca vulgaris: pulsed dye laser therapy compared with salicylic acid + pulsed dye laser therapy

Abstract: Although there was no difference between the clearance rate of the SA + PDL group and that of the PDL group after the fifth session, adding SA to PDL decreased the number of sessions to a large extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…18 In an open study, diphencyprone (DPC) 0Á1% was combined with SA 15% ointment in a trial of 50 patients with palmoplantar warts and applied for up to 4 months. The combination showed a 92% clearance in those completing the treatment, with 88% clearance in intention-to-treat cases.…”
Section: Destructive Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In an open study, diphencyprone (DPC) 0Á1% was combined with SA 15% ointment in a trial of 50 patients with palmoplantar warts and applied for up to 4 months. The combination showed a 92% clearance in those completing the treatment, with 88% clearance in intention-to-treat cases.…”
Section: Destructive Treatmentsmentioning
confidence: 99%
“…Pretreatment with SA 30% for 5 days, followed by PDL, led to faster complete clearance (2Á2 sessions in the SA-PDL group vs. 3Á1 sessions in the PDL-only group, P < 0Á05), with similar proportions of patients responding to treatment overall. 18 Two studies using PDL followed directly by intralesional bleomycin led to 60-89% wart clearance, including 80% clearance in immunosuppressed patients. 63,64 Wart location and duration may influence the rate of clearance.…”
Section: 21c Silver Nitrate (Level Of Evidence 2à)mentioning
confidence: 99%
“…60 Most patients required an average of two to three PDL sessions, and clearance rates ranged from 48.1% to 89%. 61 Therefore, combination therapies may also help to make PDL more affordable. Most authors were unable to recommend PDL as a first-line option for VV because of the one disadvantage of cost, although treatment with PDL can be less expensive in the long run than other modalities that may require more sessions to achieve complete clearance.…”
Section: Verruca Vulgarismentioning
confidence: 99%
“…Our results also indicate that IPL did not have an additional effect in itself. This corresponds with the results of one non-randomized, controlled study, which found that PDL plus salicylic acid had similar effect as PDL in the clearance of viral warts (69.7% and 66.6% of warts, respectively) after five treatment sessions at 4-week intervals [14]. Unfortunately, it is not possible to extract data on a patient level from these studies of simple warts.…”
Section: Discussionmentioning
confidence: 95%
“…Newer, non-destructive interventions such as the pulsed dye laser (PDL) and intense pulsed light (IPL) have been suggested for treatment of recalcitrant warts [5][6][7][8][9][10][11][12][13][14][15]. The mechanism of action is assumed to be selective destruction of superficially papillary capillaries of the wart as well as thermal injury of the heat-sensitive HPV [5].…”
Section: Introductionmentioning
confidence: 99%